2013
DOI: 10.5116/ijme.5259.4513
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of dental students' empathy levels in Malaysia

Abstract: Objectives: To examine the validity and reliability of the Jefferson Scale of Empathy-Health Care Provider Student version (JSE-HPS) in a sample of dental students in Malaysia, with the secondary aim of assessing empathy levels in first to final year dental students in public and private universities in Malaysia. Methods: The JSE-HPS was administered to 582 first to fifth (final) year dental students; 441 were enrolled at two public universities and 141 at a private university in Malaysia. Both descriptive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
3
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 43 publications
8
46
3
12
Order By: Relevance
“…Additional studies developed with students from different health and geographic areas [28]- [30], agree with the fact that women score higher empathy measures than men, with the exception of a study realized with dental students in Malaysia, in which differences between both genders were not found and men scored absolute values higher than women [31]. In Latin America (LA) some studies were developed about the empathy levels in different schools of dentistry and the results around the gender differences are contradictory.…”
Section: Discussionmentioning
confidence: 84%
“…Additional studies developed with students from different health and geographic areas [28]- [30], agree with the fact that women score higher empathy measures than men, with the exception of a study realized with dental students in Malaysia, in which differences between both genders were not found and men scored absolute values higher than women [31]. In Latin America (LA) some studies were developed about the empathy levels in different schools of dentistry and the results around the gender differences are contradictory.…”
Section: Discussionmentioning
confidence: 84%
“…The JSE-HPS survey is validated for health care professions, such as nursing, dentistry, and pharmacy. 12,[26][27][28] Three subconstructs underlying empathy in patient-care situations have been proposed and empirically supported: "perspective taking," "compassionate care," and "standing in the patient's shoes." 29 Specifically, this 3-factor structure was supported in Asian student samples, such as Malaysian pharmacy students 28 and Korean medical students, 23 even though a 2-factor structure emerged from a US pharmacy student sample.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of attention into the emotional component of empathy could be attributed to the inconsistencies in the level of empathy across different ethnicities and gender Ethnicities/culture can play a role in how emotions are felt and expressed in certain situation, hence understanding cultural differences is critical to appreciate emotions and to recognise the role of empathy. It has been suggested that cultural differences exist in emotional arousal level between the east and the west.…”
Section: Introductionmentioning
confidence: 99%